Genome sequencing analysis and drug resistance of the foodborne strain SCY of Bacillus cereus - QIN Xixi; LI Wen; ZHANG Wen; YUE Nan; MA Hongmei; ZENG Jin; MA Chenjie (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveThe aim of this study was to investigate the virulence and resistance of Bacillus cereus SCY isolates.MethodsB. cereus was isolated from fish dishes in a restaurant in Yinchuan using a selective medium and was named the SCY strain. After identification using PCR sequencing of the 23S rRNA gene， the genetic characteristics were analyzed by adopting second-generation whole genome sequencing technology. Next， the toxicity and drug resistance of the SCY isolate were studied using mouse studies and drug-sensitive paper experiments， respectively.ResultsThe genome size of the SCY isolate was 5.82 Mb， the number of coding genes was 5 767， and the total length of the coding region accounted for 85.50% of the whole genome. The genome of the SCY isolates contained 11 gene islands， 16 CRISPR， and five prephages； among them， 14 and 62 virulence genes were annotated in the PHI and VFDB virulence factor databases （Identity>80， Evalue<0.05）， respectively， and 215 resistance genes were annotated in the CARD resistance databases for SCY-encoded genes （Best Hit evalue<0.05）. The immunohistochemical results of the mouse intestinal tissue sections showed that the expression levels of the inflammatory factors IL-1β， CASP1， and Nlrp3 were differentially and significantly upregulated. The results of 22 bacteria antibiotic sensitivity paper tests showed that the SCY isolate was highly sensitive to chloramphenicol and clindamycin， showed an intermediary to tetracycline， cephalexin， and ampicillin， and showed resistance to 10 antibiotics， including penicillin， benzocillin， piperacillin， bacitracin， and cephalexin， and its multidrug resistance was more serious.ConclusionSCY isolates are enterotoxigenic strains， yet they carry multiple enterotoxin virulence genes and have typical multiple drug resistance characteristics. These findings provide clues for revealing the pathogenic mechanism of B. cereus isolates.